STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Achmad Shaffan Waliudin; Chusnul Chotimah; Sulistiyorini (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2023)
The principal as the manager of an educational institution has a very important strategy for carrying out coaching on teacher performance so that teachers become enthusiastic about carrying out their duties. The subject of the article is the principal, vice principal, teacher. This article shows: 1) The principal's strategy in improving teacher abilities through fostering teacher abilities in the learning process, 2) The principal's strategy in increasing teacher discipline, 3) The principal's strategy in increasing teacher motivation, namely creating a harmonious situation, fulfilling all the necessary equipment required as well as giving rewards and punishments, 4) The principal's strategy in increasing teacher commitment is to conduct training and hold meetings at the beginning of each semester and 5) Obstacles faced by school principals in improving teacher performance are: a) lack of firmness in implementing policies, b) teachers lack of motivation and remote teacher domicile, c) inadequate school facilities and d) low participation of school residents.